Diverse ecological relations of male gametophyte populations in stylar environments. Issue 3 (1st March 2016) - Harder, Lawrence D.; Aizen, Marcelo A.; Richards, Shane A.; Joseph, Michael A.; Busch, Jeremiah W.
Abstract : PREMISE OF STUDY: Pollen on a stigma represents a local population of male gametophytes vying for access to female gametophytes in the associated ovary. As in most populations, density‐independent and density‐dependent survival depend on intrinsic characteristics of male gametophytes and environmental (pistil) conditions. These characteristics and conditions could differ among flowers, plants, populations, and species, creating diverse male‐gametophyte population dynamics, which can influence seed siring and production. METHODS: For nine species, we characterized the relations of both the mean and standard deviation of pollen‐tube number at the style base to pollen receipt with nonlinear regression. Models represented asymptotic or peaked relations, providing information about the incidence and magnitude of facilitation and competition, the spatial and temporal characteristics of competition, and the intensity and relative timing of density‐independent mortality. KEY RESULTS: We infer that pollen tubes of most species competed sequentially, their tips ceasing growth if earlier tubes had depleted stylar space/resources; although two species experienced simultaneous competition. Tube success of three species revealed positive density dependence (facilitation) at low density. For at least four species, density‐independent mortality preceded competition. Tube success varied mostly within plants, rather than among plants or conspecific populations. Pollen quality influenced tube success for two of three species; affecting density‐independent survival in one and density‐dependent performance in the other. CONCLUSIONS: The diverse relations of pollen‐tube success to pollen receipt evident among just nine species indicate significant contributions of the processes governing pollen germination and tube growth to the reproductive diversity of angiosperms.